2019
DOI: 10.1038/s41598-019-50410-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of vaginal microbiome and metabolome during genital infections

Abstract: We characterized the vaginal ecosystem during common infections of the female genital tract, as vulvovaginal candidiasis (VVC, n = 18) and Chlamydia trachomatis infection (CT, n = 20), recruiting healthy (HC, n = 21) and bacterial vaginosis-affected (BV, n = 20) women as references of eubiosis and dysbiosis. The profiles of the vaginal microbiome and metabolome were studied in 79 reproductive-aged women, by means of next generation sequencing and proton based-nuclear magnetic resonance spectroscopy. Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
317
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(353 citation statements)
references
References 48 publications
29
317
3
4
Order By: Relevance
“…Several studies have suggested vaginal dysbiosis during VVC, with reduced Lactobacillus colonization rates or patterns [109,[115][116][117]. Although Lactobacillus remained dominant at the genus level, reduced rates (<67.5%) and altered species (L. crispatus progressively replaced by L. iners) were found during disease states [109,113]. The vaginal microbiome of VVC patients following antifungal treatment were also distinct, demonstrating similarities to both healthy and dysbiotic microbiomes, which might represent a transition between these states [116].…”
Section: A Role For the Microbiome?mentioning
confidence: 98%
See 3 more Smart Citations
“…Several studies have suggested vaginal dysbiosis during VVC, with reduced Lactobacillus colonization rates or patterns [109,[115][116][117]. Although Lactobacillus remained dominant at the genus level, reduced rates (<67.5%) and altered species (L. crispatus progressively replaced by L. iners) were found during disease states [109,113]. The vaginal microbiome of VVC patients following antifungal treatment were also distinct, demonstrating similarities to both healthy and dysbiotic microbiomes, which might represent a transition between these states [116].…”
Section: A Role For the Microbiome?mentioning
confidence: 98%
“…A balanced and healthy vaginal microbiome is considered to be important for maintaining female health, further influencing the health of their sexual partners and newborns, as well as the success of pregnancy and delivery [108]. Alteration in vaginal microbiome is a significant risk factor for developing diseases of the FRT, including Candida vaginitis [109]. Comprehensive studies on healthy human vaginal microbiome have identified Lactobacillus spp.…”
Section: A Role For the Microbiome?mentioning
confidence: 99%
See 2 more Smart Citations
“…The conversion of glucose and lactate to acetate and succinate by L. jensenii compared to L. crispatus , suggests that this may be an important pathomechanism of dysbiosis, altered vaginal pH, infection and infection-associated spontaneous preterm birth. Elevated amounts of acetate and succinate in the vaginal space is associated with increased pH and risk of infection such as bacterial vaginosis (Aldunate et al ., 2015; Ceccarani et al ., 2019), a known risk factor of preterm birth and other poor reproductive outcomes (Amabebe and Anumba, 2018). Vaginal bacterial communities dominated by L. jensenii usually have higher pH compared to when L. crispatus predominates (Aldunate et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%